2020
DOI: 10.1186/s13046-020-1536-x
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced histone H3 acetylation of the PD-L1 promoter via the COP1/c-Jun/HDAC3 axis is required for PD-L1 expression in drug-resistant cancer cells

Abstract: Background: Drug resistance is a major obstacle to treating cancers because it desensitizes cancer cells to chemotherapy. Recently, attention has been focused on changes in the tumor immune landscape after the acquisition of drug resistance. Programmed death-ligand-1 (PD-L1) is an immune suppressor that inhibits T cellbased immunity. Evidence has shown that acquired chemoresistance is associated with increased PD-L1 expression in cancer cells. However, the underlying mechanism is still largely unknown. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 45 publications
(61 reference statements)
1
50
0
Order By: Relevance
“…Histone acetylation is an epigenetic modification enhancing gene transcription [ 38 ]. In some drug-resistant cancer cells, hyperactivated JNK/c-Jun signaling suppressed the histone deacetylase 3 (HADC3) expression, thereby elevating the histone H3 acetylation of the CD274 promoter [ 39 ]. The HADC inhibitor had a synergistic effect with α-PD-1 in the B16F10 tumor model [ 40 ].…”
Section: Epigenetic Regulationsmentioning
confidence: 99%
“…Histone acetylation is an epigenetic modification enhancing gene transcription [ 38 ]. In some drug-resistant cancer cells, hyperactivated JNK/c-Jun signaling suppressed the histone deacetylase 3 (HADC3) expression, thereby elevating the histone H3 acetylation of the CD274 promoter [ 39 ]. The HADC inhibitor had a synergistic effect with α-PD-1 in the B16F10 tumor model [ 40 ].…”
Section: Epigenetic Regulationsmentioning
confidence: 99%
“…Other epigenetic targeting agents such as histone deacetylase inhibitors (HDACi) are also well established as candidate agents with the capacity to induce PD-L1 in cancer cells [ 161 164 ]. However, in MPM cell lines HDACi by themselves had modest effects on PD-L1, but when combined with decitabine, higher induction of this checkpoint inhibitor were observed [ 165 ].…”
Section: Outstanding Issues and Other Therapeutic Considerationsmentioning
confidence: 99%
“…In support of these observations, our results suggested that PKM2-mediated histone H3-Thr 11 phosphorylation participated in EGF-induced PD-L1 transcriptional expression. Interestingly, several studies suggested that histone H3 acetylation also play a key role in the regulation of PD-L1 gene expression in cancer cells (Lei et al, 2015;Wang et al, 2020). Given that the process of H3 phosphorylation usually recruits a histone modifying enzyme that would in turn generate the second modification (Cheung et al, 2000;Yang et al, 2012a), we supposed histone H3 acetylation may be also involved in EGFinduced PD-L1 expression in HCC cells.…”
Section: Discussionmentioning
confidence: 92%